The impact of emotional intelligence on administrator leadership practices: the role of Islamic work ethic - Shamsudin, Abdul Shukor; Abdul Rahman, Hamzah; Romle, Abd Rahim (Medwell Journal, 2016)
This study aims to examine the role of Islamic work ethic on the relationship between emotional intelligence and leadership practices among Malaysian public university administrator.Intially,the current higher education challenges require public universities to function effectively. Therefore, their employees need to equip themselves with several managerial skills such as leadership quality. Using the regular postal service, the questionnaires were sent directly to the identified respondents all over Malaysia. A total of 289 usable responses was received from a sample of 500 administrators. The collected data were analyzed using SPSS Version 19. The findings suggested that all emotional dlmensions have significant correlation with leadership practices and it is noticed that Islamic work ethic only moderates the relationship between using of emotions and leadership practices finally.The limitations and possiblefuture research were also have been discussed in this study.